Moving Images Mediating Migration as Crisis - Lynes, Krista; Morgenstern, Tyler; Paul, Ian Alan (Edition Medienwissenschaft, 2020)
In recent years, spectacular images of ruined boats, makeshift border camps, and beaches littered with life vests have done much to consolidate the politics of movement in Europe. Indeed, the mediation of migration as a crisis has worked to shore up various forms of militarized surveillance, humanitarian response, legislative action, and affective investment. Bridging academic inquiry and artistic and activist practice, the essays, documents, and artworks gathered in Moving Images interrogate the mediation of migration and refugeeism in the contemporary European conjuncture, asking how images, discourses, and data are involved in shaping the visions and experience of migration in increasingly global contexts.